Analisis Karakteristik Fisik Kopi Arabika Sidamanik Proses Pengolahan Full Washed Berdasarkan Variasi Teknik Penyangraian - Mulyara, Budi; Alwi, Annisa Lutfi; Kusumaningtyas, Rizky Nirmala (Jurnal Teknologi Agro-Industri, 2024)
Arabica coffee stands as a prominent commodity within the plantation sector, with Sidamanik Arabica coffee from Simalungun Regency, North Sumatra, showing promise for further development. Utilizing a full-washed process, which involves wet post-harvest coffee processing using water in various stages to enhance bean quality, is essential. It is imperative to uphold the quality of dry coffee beans during the roasting stage to ensure the sensory quality. The study aims to ascertain the physical characteristics of Sidamanik full-washed Arabica coffee roasted using three different techniques, incorporating initial temperatures of 170oC, 180oC, and 190oC, and a horizontal drum type machine comprising 7 mm Cast Iron material and 4 mm Food Grade Stainless Steel. Each treatment was replicated three times, and the observed variables encompassed triage value (SNI 01-2907:2008), density of green beans and roasted beans (g/cm3), and percentage of weight loss (%) of roasted beans. The data underwent analysis using the ANOVA test to determine significance, with the subsequent application of the Duncan Test at the 5% level in the presence of significant differences. The percentage of defects identified in Sidamanik Arabica coffee beans amounted to 12.33%. Furthermore, the total defect value of Sidamanik Arabica green beans was categorized as quality 3, with a total defect value of 35.7. Notably, the density value in roasted beans was higher when utilizing the Cast Iron (CI) drum type in comparison to other drum types.